Laboratory Experiments on Enhanced Oil Recovery with Nitrogen Injection - Siregar, S; Hidayaturobbi, A. D.; Wijaya, B. A.; Listiani, S N; Adiningrum, T; Irwan, Irwan; Pratomo, A I (Journal of Engineering and Technological Sciences, 2007)
Based on previous studies, nitrogen injection could recover oil up to 45-90% of initial reserves. Although this method has a very good ability to produce oil, sometimes the operation pressure is higher than leak off formation pressure. In this study, operation pressure used a low pressure to solve this problem under immiscible process. Objective of this study is to determine the effect of injection pressure and displacement rate on oil recovery performance of continuous one dimensional nitrogen gas injection with a slim tube apparatus. The effect of nitrogen gas-oil contact on the gas composition was investigated using Gas Chromatograph Mass Spectrometer apparatus. In the experiments, nitrogen gas was injected into an oil sample of 38.5 oAPI gravity at various rates: 20 cc/hr, 30 cc/hr and 36.66/hr under 1500 psi pressure, and then at 20 cc/hr undr 2500 psi pressure. The results showed that an increase in injection rate increased oil recovery factor. The recovery factor lies between 40-54% of original oil in place. Gas analysis before injection and at the injection outlet showed a change of composition. when oil was contacted by nitrogen, indicating that some molecular mass transfer had taken place.